Developing Global Supply Chain Manager for Business Expansion - Wulansari, Puspita; Fernando, Yudi (IGI Global USA, 2018)
Global competition has forces companies to continuously innovate by frequently asses and improve their supply chain processes, flexibility and fast delivery as effectiveness required in each supply chain processes. This is to ensure cost efficiency, faster delivery and in the end would lead to customer satisfaction and perform better than competitors. To be able to perform better among competitors and improving firms supply chain performance, firms need the talents who able to manage global resources effectively and understand culture, suppliers/ workers attitude and comply with global regulations. Success implementation of global supply chain has linked with talents capability to maximize manage global resources. The aim of this chapter is to discuss the competency needed of global supply chain managers to support international business expansion.